INTRODUCTION TO FLUID MECHANICS - Mansurov Mahkamadyakub Kunduzovihc (Galaxy International Interdisciplinary Research Journal, 2023)
Mechanics is the oldest physical science that deals with both stationary and moving bodies under the influence of forces. The branch of mechanics that deals with bodies at rest is called statics, while the branch that deals with bodies in motion is called dynamics.